The Ritualization of Consumer Capitalism: Catherine Bell's Ritual Theory, Ritual Practice in the Age of Starbucks - Gonzalez, George (Implicit religion, 2015)
According to Max Weber, within the differentiated order of modernity, instrumental reason (Zweckrationalitat) came to dominate economic life (as well as law, science and architecture). Weber juxtaposed instrumental reason against religious, traditional and affective life. However, the history of consumption, past and present, challenges these distinctions. A major feature of neoliberalism is the increasingly explicit and self-reflexive ritualization of consumption, such that paradigms of ritual and consumption appear to cohere. The primary focus of this article does not lie in the mechanics of consumer rituals themselves, as an empirical matter, but, instead, in the conceptual entailments that exist between contemporary discourses of ritual and branding. Taking Starbucks as a case study, the article notes some key similarities between Catherine Bell's discussion of ritualization and contemporary branding theory and practice, suggesting the possibility that religious studies and marketing share a similar epistemic context which also implies that our own intellectual labors as scholars of religion are enmeshed in the logic and doings of capital. A method for materializing religious studies within contemporary late capitalist conditions, which is deemed urgent, is therefore also proposed.